The Settlement of Contradictory Hadith on Mahram Status for Man due to Al-Radhāah - Zikri Darussamin; Rahman Rahman; Adynata Adynata (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study examined the hadith regarding the determination of mahram status for adult men due to breastfeeding (al-radhāah). It was needed to be conducted because the hadiths are contradictory to one another. Using the mukhtalif al-hadith science method, this study tried to find the right and correct understanding, avoiding visible outward contradictions, with two forms of settlement, namely non-compromising and compromise. The majority of scholars prioritize a compromise settlement first, then a non-compromising one. The determination of the hadith